2011
DOI: 10.1111/j.2041-1626.2011.00103.x
|View full text |Cite
|
Sign up to set email alerts
|

Neutralizing effect of green tea epigallocatechin‐3‐gallate on nicotine‐induced toxicity and chemokine (C‐C motif) ligand 5 secretion in human oral epithelial cells and fibroblasts

Abstract: The present study suggests that epigallocatechin-3-gallate, the major polyphenol in green tea, may represent a novel preventive/therapeutic agent for smoking-related periodontitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 56 publications
(109 reference statements)
1
16
0
Order By: Relevance
“…Evidence from mechanistic studies on green tea indicates that the high EGCG content has anti‐oxidant, anti‐microbial and anti‐collagenase effects, all of which could help to prevent periodontal diseases (Venkateswara et al . ) and smoking‐related gum disease (Desjardins & Grenier ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence from mechanistic studies on green tea indicates that the high EGCG content has anti‐oxidant, anti‐microbial and anti‐collagenase effects, all of which could help to prevent periodontal diseases (Venkateswara et al . ) and smoking‐related gum disease (Desjardins & Grenier ).…”
Section: Methodsmentioning
confidence: 99%
“…Black and green teas are thought to have anti-cariogenic effects through reducing inflammation and preventing the adhesion and growth of bacteria linked with periodontal disease (Hamilton-Miller 2001;Chatterjee et al 2010). Evidence from mechanistic studies on green tea indicates that the high EGCG content has anti-oxidant, anti-microbial and anti-collagenase effects, all of which could help to prevent periodontal diseases (Venkateswara et al 2011) and smoking-related gum disease (Desjardins & Grenier 2012).…”
Section: Oral Healthmentioning
confidence: 99%
“…Both in vitro and in vivo administration of green tea in smokers improved the levels of anti‐oxidant enzymes in saliva . Recently, the effects of EGCG on the nicotine‐induced toxic and inflammatory responses in oral epithelial cells and gingival fibroblasts were investigated . Nicotine was used either alone or in combination with the lipopolysaccharide of Aa.…”
Section: Green Tea As a Functional Food For Oral Health In Older Adultsmentioning
confidence: 99%
“…Nicotine was used either alone or in combination with the lipopolysaccharide of Aa. It was found that pretreatment of cells with EGCG neutralized the nicotine‐induced toxicity in epithelial cells and fibroblasts . It even inhibited acrolein induced apoptosis in human gingival fibroblasts …”
Section: Green Tea As a Functional Food For Oral Health In Older Adultsmentioning
confidence: 99%
See 1 more Smart Citation